Understanding Artificial Sweeteners and Food Colorants-their Impact on Human Health: A Review - Puttegowda, Satish Kumar Basattikoppalu; Shivaramu, Mohith; Manjunath, Balaji Skanda; Venkataraman, Rajesh; Nagarajappa, Ravindra Basaralu (Indian Journal of Pharmacy Practice)
This review article comprehensively explores the overview of artificial sweeteners and food colorants, examining their safety, regulatory status, and potential health effects. It explores the historical background of artificial sweeteners, covering key compounds like saccharin, aspartame and cyclamate, while also highlighting emerging alternatives such as rare sugars. The discussion extends to the physiological impacts of artificial sweeteners including their potential ill effects on blood glucose levels, obesity, gut microbiome, cardiovascular health, and cancer risk. Additionally, the review evaluates the safety and adverse effects of food colorants, emphasizing regulatory frameworks and potential health risks associated with synthetic food colorants like tartrazine and rhodamine B. It concludes by underlining the importance of cautious consumption, particularly among vulnerable populations like children and pregnant women, and advocates for ongoing research to inform evidence-based dietary guidelines and regulatory policies.
Keywords: Artificial Sweeteners; Food Colorants; Rare Sugar; Diabetes; Obesity; Cancer